2019
DOI: 10.1088/1742-6596/1358/1/012079
|View full text |Cite
|
Sign up to set email alerts
|

Routing problem in rectangular mesh network using shortest path based Greedy method

Abstract: A supercomputer can have thousands of processor-memory pairs which often referred as processing pins. Each of these pins is connected to each other through networks and passes message using a standard message passing mechanism such as Message Passing Interface. In this research, we consider the routing problem in rectangular mesh network. Each terminal pin in the network needs to be connected with its destination pin for it to function properly. Thus, maximizing the number of connection for each pair of pins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In the visibility graph, the obstacles are represented as polygons [ 50 ], and the vertical nodes of the polygonal obstacles are connected in such a way that the path length is minimized while the lines remain close to the obstacles. In contrast, the Voronoi graph uses the two closest points of the edges of the obstacles for planning and divides the domain into subdomains.…”
Section: Classic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the visibility graph, the obstacles are represented as polygons [ 50 ], and the vertical nodes of the polygonal obstacles are connected in such a way that the path length is minimized while the lines remain close to the obstacles. In contrast, the Voronoi graph uses the two closest points of the edges of the obstacles for planning and divides the domain into subdomains.…”
Section: Classic Approachesmentioning
confidence: 99%
“…Then, based on Darwinian evolutionary theory, they generate a new population using the three genetic operators (mutation, crossover, and selection). The new populations are created until the stopping conditions are met [ 50 ]. Such stopping conditions are a time limit, the required fitness value, and the maximum number of generations.…”
Section: Heuristic Approachmentioning
confidence: 99%
“…In the visibility graph, the obstacles are represented as polygons [15]. Te vertical of the polygonal obstacles have nodes connected.…”
Section: Artifcial Potential Field Khatibmentioning
confidence: 99%
“…An improvement of this method and its application in path planning have been presented in Fan and Shi [14], and it has been shown that the upgrades are reasonable and practical. Finally, in [15], the path planning problem in rectangular mesh networks was addressed by fnding the shortest link between each pair of sites using a Dijkstra-based greedy algorithm. [16] introduced the artifcial potential feld (APF) method for the mobile robotics problem by believing the divergences between attraction and repulsion forces help robot movement inside the environment.…”
Section: Dijkstra's Algorithm Edsger Wybe Dijkstra Introducedmentioning
confidence: 99%